Quality Improvement of Sample Collection Increases the Diagnostic Accuracy of Quantitative Fecal Immunochemical Test in Colorectal Cancer Screening: A Pilot Study - Zhou, Ru-chen; Wang, Pei-zhu; Li, Yue-yue; Zhang, Yan; Ma, Ming-jun; Meng, Fan-yi; Liu, Chao; Yang, Xiao-yun; Lv, Ming; Zuo, Xiu-li; Li, Yan-qing (Frontiers in Medicine, 2021)
Objective: The diagnostic efficiency of quantitative fecal immunochemical test (qFIT) has large variations in colorectal cancer (CRC) screening. We aimed to explore whether practical sample collection operant training could improve the diagnostic accuracy of qFIT in CRC screening. Methods: Moderate/high-risk individuals aged 50-75 years old were invited to participate in a prospective observational study between July 2020 and March 2021. Participants took a qFIT sample without fecal sample collection operant training in advance, and then completed another qFIT sample after operant training. The primary outcome was the sensitivity and specificity of qFITs for CRC and advanced colorectal neoplasia (ACRN). The secondary outcome was the difference in the areas under the curves (AUCs) and the fecal hemoglobin concentrations between the qFIT without and after operant training. Results: Of 913 patients, 81 (8.9%) had ACRN, including 25 (2.7%) with CRC. For CRC, the sensitivities of qFIT without and after operant training at 10 µg/g were 80.4% and 100.0%, respectively, and the specificities were 90.1% and 88.4%, respectively. For ACRN, the sensitivities were 49.4% and 69.1%, and the specificities were 91.7% and 91.3%, respectively. The AUC of qFIT after operant training was significantly higher than that without operant training for CRC (P=0.027) and ACRN (P=0.001). After operant training, the fecal hemoglobin concentration was significantly higher than that without operant training (P=0.009) for ACRN, but there was no significant difference for CRC (P=0.367). Conclusion: Practical sample collection operant training improves the diagnostic accuracy of qFIT, which increases the detection of low concentrations of fecal hemoglobin. Improving the quality of sample collection could contribute to the diagnostic efficiency of qFIT in CRC screening.